Системна оцінка та прогнозування підтоплення території на основі персептронних моделей - Ковальчук, П.І.; Шевчук, С.А.; Ковальчук, В.П. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2010)
System assessment methodology and underflooding territories forecasting based on perceptron models which computational and linguistic assessments used were proposed. Information technology is worked out based on inductive modeling principle. Model complex of technology was identified and tested with researching dates in 2008-2010 Kherson region s Kalanchak.